Comparison between homemade stain remover and commercial stain remover for textiles / Nur Syaliza Musa … [et al.] - Musa, Nur Syaliza; Abdurahman, Nor Liyana; Zainal Abidin, Zahirah; Adnan, Farah Hanim; Nasir, Eryna (UiTM Press for the Research Management Center (IRMI), Universiti Teknologi MARA, 2021)
Stain remover is used to remove or masks stain from textiles. Two types of textile stain removers were compared in this study; store bought and home prepared types. Due to the environmental and health issues associated with commercial household cleaners, as well as costly, there have been attempts by consumer especially housewives to prepare cleaning products by using materials which can be found in the kitchens. Hence, the main objective of this study is to compare the effectiveness of home prepared textile stain remover with commercial stain remover by assessing the stain properties on cotton and polyester fabrics. Two different brands of stain remover and easily found materials were applied on these two fabrics. The stains on the fabrics were then assessed according to AATCC Test Method 130 and by using chromameter for the intensity of the stain after cleaning. The results showed that, for the cotton fabric, the most effective stain remover is Commercial Brand 1. Commercial Brand 1 and vinegar with baking soda demonstrated an encouraging effect on polyester fabric. The commercial textile stain remover shows great cleaning effect on both cotton and polyester, while home prepared stain remover has limited ability to clean the stains on cotton. However, its cleaning effect on polyester is equivalent to a commercial product